Genesis 1-11 - Carr, David McLain (International Exegetical Commentary on the Old Testament (IECOT), 2021)
"This commentary offers a synthesis of close readings of Genesis 1-11 and up-to-date study of the formation of these chapters in their ancient Near Eastern context. Each interpretation of these evocative and multilayered narratives is preceded with a new translation (with textual and philological commentary) and a concise overview of the ways in which each text bears the marks of its shaping over time. This prepares for a close reading that draws on the best of older and newer exegetical insights into these chapters, a reading that then connects to feminist, queer, ecocritical, and other contemporary approaches."